MANAJEMEN HUBUNGAN MASYARAKAT BERBASIS DIGITAL UNTUK PENINGKATKAN PUBLIKASI DAN PENCITRAAN PONDOK PESANTREN SABILURROSYAD GASEK - Muhammad Syifa' Nurdi (Ulul Amri: Jurnal Manajemen Pendidikan Islam, 2023)
The acceleration of information arising from the industrial revolution 4.0 has indirectly influenced organizations to compete to reach targets of organizational interests. On the other hand, in the face of the accelerated flow of information, the community realizes that they need a variety of quality information services. This phenomenon is an opportunity for organizations and public services to always provide interesting information to the public in order to improve their form of public relations and to improve the image of the organization or institution. Islamic boarding schools must not be apathetic in responding to this era of digital transformation. Islamic boarding schools must be able to follow this era, where information and communication technology is ingrained in society. Islamic boarding schools need to improve in order to implement digital-based public relations management. Digital information and communication media can be used by Islamic boarding schools to convey information such as profiles, vision and mission, facilities, programs, activities, and their advantages. This article discusses the use of technology as a form of public relations in Islamic boarding schools. Digital-based public relations management can be a big opportunity for Islamic boarding schools.